Nerve Growth Factor Involves Mutual Interaction between Neurons and Satellite Glial Cells in the Rat Trigeminal Ganglion - Kurata, Sayaka (Japan Society of Histochemistry and Cytochemistry, 2013)
Nerve growth factor (NGF) plays a critical role in the trigeminal ganglion (TG) following peripheral nerve damage in the oral region. Although neurons in the TG are surrounded by satellite glial cells (SGCs) that passively support neural function, little is known regarding NGF expression and its interactions with TG neurons and SGCs. This study was performed to examine the expression of NGF in TG neurons and SGCs with nerve damage by experimental tooth movement. An elastic band was inserted between the first and second upper molars of rats. The TG was removed at 0–7 days after tooth movement. Using in situ hybridization, NGF mRNA was expressed in both neurons and SGCs. Immunostaining for NGF demonstrated that during tooth movement the number of NGF-immunoreactive SGCs increased significantly as compared with baseline and reached maximum levels at day 3. Furthermore, the administration of the gap junction inhibitor carbenoxolone at the TG during tooth movement significantly decreased the number of NGF-immunoreactive SGCs. These results suggested that peripheral nerve damage may induce signal transduction from neurons to SGCs via gap junctions, inducing NGF expression in SGCs around neurons, and released NGF may be involved in the restoration of damaged neurons.